Effectiveness of Trauma Healing Therapy for Victims of Natural Disasters - Rihartono, Anisa Nur Khalifah; Afriyanti, Desi; Syafhira, Aureal; Salamah, Naila Umi; Ningsih, Septiya; Yanmar, Siti Anisah (Journal of Language and Health, 2024)
Natural disasters like earthquakes, tsunamis, and floods have a significant psychological impact on both children and adults. Trauma healing aims to help victims cope with post-traumatic stress symptoms such as anxiety, flashbacks, insomnia, and emotional disturbances. For children, methods like play, art, and group activities are used to calm emotions, create safety, and help them express fears, manage emotions, and build self-confidence. For adults, trauma healing typically includes cognitive behavioral therapy (CBT), counseling, and exposure therapy to reduce trauma triggers. This study used a systematic review of articles from various databases, including Google Scholar, to gather relevant evidence published between 2020 and 2024. The results show that trauma healing is an effective, multidimensional approach, addressing psychological, social, cultural, and spiritual needs. It is tailored to different target groups such as children, adolescents, and adults. Trauma healing is essential for reducing anxiety and rebuilding confidence in disaster victims. Methods like play therapy and community-based approaches support individual and collective recovery. Prioritizing trauma healing in disaster response ensures comprehensive recovery and contributes to community resilience.